Peningkatan Kesehatan dan Keselamatan Kerja di Dapur Pada Ibu-Ibu Dusun Pucung dan Nglaos, Kemadang, Tanjungsari, Gunungkidul, Daerah Istimewa Yogyakarta - Emaputra, Andrean; Sulistyaningsih, Eka; Sekarjati, Kartinasari Ayuhikmatin; Yusuf, Muhammad; Saudah, Siti; Asih, Endang Widuri; Rif`ah, Mega Inayati; Saputro, Widodo (STIKES Yayasan RS.Dr.Soetomo, 2025)
Occupational Health and Safety (OHS) is very important to be implemented in the household environment, especially in the kitchen. Mothers in Pucung and Nglaos, Kemadang, Tanjungsari, Gunungkidul, Special Region of Yogyakarta carry out cooking activities for daily needs and process products from seaweed. These activities have potential hazards, such as fire, burns, exposure to sharp objects, etc. Therefore, these mothers need to receive training on OHS to maintain their health and safety at work in the kitchen. To fulfill this, a team of lecturers and students from AKPRIND Indonesia University conducted community service activities on OHS. This activity was carried out through three stages, namely: (1) delivery of material on occupational health and safety OHS, (2) questions and answers about the material, and (3) cooking demonstrations in accordance with OHS rules. This activity received very high enthusiasm and was attended by 40 participants and was able to increase their knowledge of occupational health and safety OHS in the kitchen. Things that need to be done to maintain OHS in the kitchen are providing a light fire extinguisher (APAR), burn ointment, face field, apron, lighting, ventilation, sink, mop, red medicine, trash can, and emergency lights.